Clinical study of primary caesarean section among multigravida in a tertiary care hospital - Kumar, Rajesh; Chaudhary, Rachna; Dhama, Vandana; Singh, Shakun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Primary caesarean section in multigravida refers to first time caesarean section in multiparous women who have had previous one or more vaginal delivery. The study focused on the frequency, indication, intra operative and postoperative complications, maternal and fetal outcome of primary caesarean section in multiparous women with previous vaginal deliveries. Methods: It was a prospective study of all the cases of primary caesarean section in multigravida admitted at LLRM Medical College Meerut, Uttar Pradesh over period of 1 year from January 2021 to December 2021. Results: Total number of deliveries during the study period of 1 year was 5670 and total no of caesarean section was 2432 with a caesarean rate of 42.89%. Out of 2432 caesarean section 488 (20.10%) were done in primigravida and 253 (10.40%) in multigravida. In present study most common indication for caesarean section was malpresentation 68 (26.86%) followed by severe oligohydramnios in 47 (18.57%). Most common maternal complication was pyrexia in 24 (9.48%). Most common morbidity were due to preterm 65 (22.13%) neonates followed by RDS in 22 (8.69%) neonates. Conclusions: Though responsible for least number of overall caesarean section, multiparous subjects undergoing primary caesarean section is high risk pregnancy with possibility of adverse obstetric outcome in significant number of subjects and hence multiparous women deserve the same attention during pregnancy and labour as primigravida and women with repeat caesarean section.